How Can Physical Activity Be Promoted Among Children and Adolescents? A Systematic Review of Reviews Across Settings - Messing, Sven; Rütten, Alfred; Abu-Omar, Karim; Ungerer-Röhrich, Ulrike; Goodwin, Lee; Burlacu, Ionuţ; Gediga, Günther (Frontiers in Public Health, 2019)
Introduction: A vast majority of children and adolescents are physically inactive. As a result, high obesity rates and related diseases have made physical activity promotion a politically relevant topic. In order to form the basis for political decision making, evidence is required regarding the efficacy and effectiveness of interventions for physical activity promotion. In contrast to previous research, this systematic review of reviews targets three key settings (family and home, childcare, school), and is among the largest to have been conducted. Methods: A systematic review of reviews was conducted as part of a large-scale project to develop national recommendations for physical activity promotion in Germany. Six electronic databases were searched and inclusion criteria were defined. Two independent reviewers screened the titles and abstracts of potentially relevant literature. 213 reviews were identified and categorised by target group. A total of 74 reviews were identified dealing with children and adolescents. Each review underwent a quality assessment. Results: 39 reviews with the highest quality and relevance were analysed. Three reviews focused on the family and home setting, 4 on the childcare setting, 28 on the school setting and 4 on other settings. Evidence revealed the key role played by parents in promoting physical activity in children within each setting. Furthermore, evidence pointed toward the efficacy of multi-component interventions in the childcare and school setting. Several evidence-based intervention strategies were identified for childcare facilities and schools. Discussion: The review of reviews identified a number of promising strategies for PA promotion among children and adolescents. Among reviews, multi-component interventions in childcare facilities and schools stand out prominently. At the same time, the review of reviews indicated that there is still a lack of studies on the efficacy of interventions that go beyond the individual level. We recommend that future research should also target community and policy level interventions and interventions other than the school setting. In order to make more specific recommendations regarding the scale-up of promising intervention strategies, further knowledge about the effectiveness, health equity and cost effectiveness of interventions is needed.